Comparison of Overridden Medication-related Clinical Decision Support in the Intensive Care Unit between a Commercial System and a Legacy System - Wong, Adrian; Wright, Adam; Seger, Diane L.; Amato, Mary G.; Fiskio, Julie M.; Bates, David (Applied Clinical Informatics, 2017)
Background: Electronic health records (EHRs) with clinical decision support (CDS) have shown to be effective at improving patient safety. Despite this, alerts delivered as part of CDS are overridden frequently, which is of concern in the critical care population as this group may have an increased risk of harm. Our organization recently transitioned from an internally-developed EHR to a commercial system. Data comparing various EHR systems, especially after transitions between EHRs, are needed to identify areas for improvement.Objectives: To compare the two systems and identify areas for potential improvement with the new commercial system at a single institution.Methods: Overridden medication-related CDS alerts were included from October to December of the systems’ respective years (legacy, 2011; commercial, 2015), restricted to three intensive care units. The two systems were compared with regards to CDS presentation and override rates for four types of CDS: drug-allergy, drug-drug interaction (DDI), geriatric and renal alerts. A post hoc analysis to evaluate for adverse drug events (ADEs) potentially resulting from overridden alerts was performed for ‘contraindicated’ DDIs via chart review.Results: There was a significant increase in provider exposure to alerts and alert overrides in the commercial system (commercial: n=5,535; legacy: n=1,030). Rates of overrides were higher for the allergy and DDI alerts (p<0.001) in the commercial system. Geriatric and renal alerts were significantly different in incidence and presentation between the two systems. No ADEs were identified in an analysis of 43 overridden contraindicated DDI alerts.Conclusions: The vendor system had much higher rates of both alerts and overrides, although we did not find evidence of harm in a review of DDIs which were overridden. We propose recommendations for improving our current system which may be helpful to other similar institutions; improving both alert presentation and the underlying knowledge base appear important.Citation: Wong A, Wright A, Seger DL, Amato MG, Fiskio JM, Bates D. Comparison of Overridden Medication-related Clinical Decision Support in the Intensive Care Unit between a Commercial System and a Legacy System. Appl Clin Inform 2017; 8: 866–879 https://doi.org/10.4338/ACI-2017-04-RA-0059
Keywords: Adverse drug event; Clinical decision support; Critical care; Informatics; Patient safety